N6-methyladenine DNA modification modulates pathogen virulence in nematodes - Dadong Dai; Shurong Zhang; Boyan Hu; Yayi Zhou; Simeng Cui; Jia Sun; Yali Zhang; Xueyu Wang; Shahid Siddique; Dexin Bo; Min Zhang; Valerie M. Williamson; et al. (Proceedings of the National Academy of Sciences, 2026)
Understanding the global regulatory mechanisms that control pathogen virulence gene expression is essential for elucidating the molecular basis of pathogenicity. N6-methyladenine (6 mA) plays a crucial role in regulating gene expression in response to various environmental stresses; however, its role in pathogen virulence remains largely unexplored. Here, we report the widespread occurrence of 6 mA across 17 nematode isolates and map its genomic landscape in six notorious agriculturally important pathogen root-knot nematodes (RKNs). We demonstrated that 6 mA is characterized by a conserved GAG motif across nematodes, but exhibits species-specific distribution patterns and distinct effects on gene expression. In particular, its enrichment in transposable elements (TEs) differs between polyploid and diploid nematodes, suggesting lineage-specific epigenetic regulation potentially associated with polyploidy. We further identified two functional 6 mA demethylases, MiNMAD-1 and MiNMAD-2, and confirmed their catalytic activity and active sites. Host-induced gene silencing (HIGS) of minmad-1 significantly increased plant resistance to three polyploid RKN species. A detailed functional analysis revealed that minmad-1 knockdown broadly affected gene expression during the parasitic stage, including genes involved in virulence, thereby reducing nematode infectivity. Together, our findings suggest 6 mA demethylase as a key epigenetic regulator of RKNs’ virulence, providing new insights into nematode biology and offering promising targets for the development of sustainable control strategies.